Waterborne polyurethanes from self-catalytic tartaric acid-based polyols for environmentally-friendly sizing agents. (October 2021) - Dai, Shengtao; Li, Peikun; Li, Xuyang; Ning, Chen; Kong, Lingqiang; Fang, Lanqing; Liu, Yu; Liu, Liu; Ao, Yuhui
Abstract: A novel self-catalytic waterborne polyurethane (WPU) was designed and utilized to prepare sizing agent for carbon fibers (CF). The carboxy modified long-chain diol (CMLCD) with capacity of self-catalysis was synthesized through esterification reaction, serving as not only the reactant, but also catalyst to facilitate the reaction between the hydroxyl and isocyanate groups, avoiding the employment of highly toxic catalyst for the preparation of WPU. Meanwhile, a bio-based tartaric acid was utilized for developing self-catalytic WPU, preventing the negative effect of catalyst which was difficult to remove in the process of WPU synthesis. Compared with the unsized CF composites, the tensile strength, flexural strength and izod impact strength of 1.0 wt% WPU-sized CF composites reached 132.1 MPa, 208.3 MPa and 7.65 kJ/m 2, showing an increase of 14.3%, 24.4% and 119.6%, respectively. This study contribute an attractive way for potential industrial production and application of green WPU sizing agent. Highlights: ∙ The self-catalysis bio-based polyurethane sizing agents for CF/PA6 were prepared. ∙The carboxy modified long-chain diol (CMLCD) with capacity of self-catalysis was synthesized through esterification reaction. ∙Tartaric acid (TA), a cheap, natural and easily accessible reagent from the processing of grapes wine was used to replace dimethylopropionic acid (DMPA). ∙The tensile strength, bending strength and izod impact strength were increased by 14.3%, 24.4% and 119.6%, as compared with unsized CF/PA6 composites.